Limnology and biota of Lake Yindarlgooda - an inland salt lake in Western Australia under stress - Campagna, Veronica (Curtin University, 2007)
Inland salt lakes of the arid and semi-arid zones of Western Australia are unique systems. An unpredictable rainfall pattern and a transient water regime ensure these lakes remain dry for much of the year. Lake Yindarlgooda in the Eastern Goldfields of Western Australia is a typical inland salt lake that has been subjected to additional stresses. This thesis is the outcome of investigations conducted on the lake from 2001 to 2003. Emphasis is on the limnology and biota of the lake, including an adjacent wetland, and impacts on the aquatic ecosystems caused predominantly by mining. Lake Yindarlgooda is a large, shallow hypersaline lake situated on the Yindarlgooda Palaeoriver. It is sodium chloride dominated and has naturally high background levels of nickel. Sites impacted by the leaching of hypersaline decant water from a leach residue storage facility (LRSF) were differentiated from control sites using multivariate statistics. Salinity was found to be a major determinant in the structure of the biological communities in the lake systems.Different biotic communities with low taxonomic diversity were recorded in Lake Yindarlgooda and Swan Refuge, a nearby hyposaline clay pan. The benthic microbial communities were dominated by halotolerant diatoms, notably Amphora coffeaeformis, Navicula incertata and Hantzschia baltica. Variation in the diatom assemblages between the playa sites and the clay pan were noted, influenced by habitat type and salinity. Within Lake Yindarlgooda, the diatom assemblages in the control and impact sites were found to be similar. A narrow salinity spectrum dictated the taxa present. Many of the benthic diatoms collected during the dry phase were encysted, having entered dormancy. The invertebrate fauna in Lake Yindarlgooda and Swan Refuge belonged to the Crustacea. A larger percentage of hyposaline invertebrate taxa were recorded from Swan Refuge, while those in Lake Yindarlgooda were typically halotolerant species. The Ostracoda showed the greatest diversity and their abundance was higher in the southern control sites while the Anostracan, Parartemia sp., dominated the northern impact sites of the playa.The riparian zone of Lake Yindarlgooda supported a diverse plant community, dominated by the Chenopodiaceae. The marginal vegetation communities along the shores of Lake Yindarlgooda were found to be similar, indicating habitat homeogeneity. Within the riparian zone both biological and physical soil crusts occupied large areas not inhabited by vascular plants. The biological soil crust identified was composed of an association between the filamentous cyanobacterium Microcoleus sp. and a moss species (Musci). Both biological and physical soil crusts were found to have functional roles in stabilising the surrounding low dunes. The soil crusts in the northern control sites were badly degraded as a result of trampling by livestock, while those in the southern control sites were protected and were intact. Only one Parartemia species was found to inhabit Lake Yindarlgooda, Parartemia n. sp. d. It was collected in salinities ranging from 50 to 140 g L-1. The population appeared to be oviparous, recruitment mostly from resting eggs. The male to female ratios varied between sites, as did the number of juveniles compared to the adults. The northern impact sites had a more mature Parartemia population than the southern control sites and appeared to have undergone a second recruitment. Examination of the surface sediment found a well established Parartemia “egg bank” in the northern impact sites with egg numbers much higher than in the southern control sites.The ultrastructure of the Parartemia resting egg was identical to that of Artemia. Differences in the external features and internal structure of the resting egg of Parartemia n sp. d and Parartemia n. sp g from Lake Miranda, another saline lake, were identified. This study showed morphological variation of the egg within Parartemia, a finding not previously recorded. Rehydration trials on the Parartemia egg bank indicated that the increase in sediment salinity from the LRSF had a negative effect on the hatching of the resting eggs. In salinities above 60 mS cm-1 hatching was less successful. The conditions provided in the trials were similar to those in Lake Yindarlgooda. The hatching technique was repeated on sediment from Lake Miranda with similar results. These trials were considered a valuable monitoring tool in the assessment of impacts on the biota of temporary lakes in the absence of water. This study demonstrated that in the absence of water the egg and spore/seed bank can be used as a proxy for monitoring temporary lakes. It was also found to be valuable in understanding the distribution and diversity of the biotic communities in Lake Yindarlgooda. This study provides the first integrated reference information on a Western Australian inland salt lake against which any future impact may be assessed.